Hermeneutical approach as a methodological basis of soft skills development of technical students - Polina G. Labzina; Svetlana G. Menshenina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Increased requirements of employers forced researchers to pay attention to the lack of academic knowledge and professional competence, so-called hard skills, when applying for a job. Multitasking has become a defining trend in all professional fields, which confronts professionals with problems that do not have a solution algorithm. We need special mechanisms for adapting the employees to constant challenges and additional knowledge and skills, the function of which is performed by soft skills. This article focuses on the development of creative and critical thinking as one of the categories of soft skills, as it is the style of thinking that determines the level of success in the professional sphere. Today, with the development of the information society, the problem of understanding a large amount of information, its processing, correct interpretation by students and further adaptation for application in professional field is a crucial one. Communication in the field of science and technology is realized in the form of discourse, which actualizes the development of future graduates creative thinking through the ability formation to explicate meaningful content, decode and deverbalize in the process of perceiving, understanding and interpreting professionally relevant information when working with scientific and technical discourse. The discipline of "Foreign Language" provides the necessary environment for developing soft skills working with the discourse in question. In this case reading is a tool for obtaining information by comparison, comparing data, analyzing the information received, highlighting the main and secondary information, establishing causality, assessing. The hermeneutic approach to the development of soft skills ensures the optimal conditions to activate mental operations responsible for effective perception and further adaptation of the information received for professional purposes. Practical part of the research is to compile a set of tasks for working with text material, which will ensure the information understanding and interpretation through certain reading strategies stimulating mental activity.